Enhancement of VEGF on Axial Vascularization of Nano-HA/Collagen/PLA Composites: A Histomorphometric Study on Rabbits - Xiao Chang; Hai Wang; Zhihong Wu; Xiaojie Lian; Fuzhai Cui; Xisheng Weng; Bo Yang; Guixing Qiu; Baozhong Zhang (International Journal of Polymer Science, 2014)
The aim of this study was to investigate whether the nanohydroxyapatite/collagen/poly(L-lactic acid) (nHAC/PLA) composite is suitable to be compounded with VEGF to enhance the axial vascularization in vivo. Thirty rabbits were divided into 2 groups of 15 animals each. In control group, a nHAC/PLA scaffold slice was vascularized axially by an inserted ligated femoral arteriovenous (AV) bundle in the animal. In experimental group, a slice compounded with VEGF gel was applied. The rabbits were sacrificed at 2 weeks, 6 weeks, and 10 weeks after surgery; the specimens of scaffold slices underwent histomorphometric examination; analysis of the microvessel density (MVD) of both groups was done. The combination with VEGF (Group B) did not enhance the vascularization in early phase (2 and 6 weeks, P>0.05) but worked in later phase (10 weeks, P<0.05). The data of the experiment demonstrated the suitability of the nHAC/PLA composite as carrier for the growth factor VEGF, enabling its sustained release in bioactive form with enough binding efficacy.